2013
DOI: 10.1080/01652176.2013.772315
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of clindamycin hydrochloride in homogenates of normal dog skin when administered at two oral dosage regimens

Abstract: Background: Clindamycin is frequently used for the treatment of bacterial pyoderma. Objective: To compare the pharmacokinetics of clindamycin in whole skin homogenates of normal dogs when administered orally at two dosage regimens (5.5 mg/kg BW, twice daily and 11 mg/kg BW, once daily). Animals and Methods: Skin biopsies were obtained from six laboratory beagles before, 3, 6 and 12 h after the first and the fifth dose of clindamycin at the former regimen, as well as before, 3, 6, 12 and 24 h after the first an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The AUC reported by Saridomichelakis were 30.1 [32] and 18.8 [33] (μg * h)/mL. The AUC values found in the present study were: 124.01 (μg * h)/mL and 96.98 (μg * h)/mL for ERF1 and ERF2, respectively.…”
Section: Parameter Control Treatment Erf1 Erf2supporting
confidence: 58%
See 2 more Smart Citations
“…The AUC reported by Saridomichelakis were 30.1 [32] and 18.8 [33] (μg * h)/mL. The AUC values found in the present study were: 124.01 (μg * h)/mL and 96.98 (μg * h)/mL for ERF1 and ERF2, respectively.…”
Section: Parameter Control Treatment Erf1 Erf2supporting
confidence: 58%
“…Additionally, a recent study has reported that a topical gel containing an antibacterial agent (clindamycin) and an antifungal agent (butoconazole) as a treatment for vaginal infections achieved controlled release for up to 10 days in humans [31]. With respect to pharmacokinetic parameters, the Cmax reported in the studies by Saridomichelakis were 3.812 μg/mL [32] and 3.05 μg/mL [33]; in comparison, a higher Cmax was obtained for ERF1 in this study: 7.51 μg/mL. In another study [34], a Cmax value of 4.4 μg/mL was observed for IM administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation